(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Non-obstructive azoospermia (NOA) is considered as the most severe form of male infertility. The rate of sperm retrieval from NOA men after mTESE surgery is still only ranging from 30% to 60%. In case sperm is not found, which can have unexpected repercussions for to the patient such as: pain, testicular damage, endocrine impairment, and costly expenses... Therefore, predicting the sperm retrieval rate (SSR) is crucial for NOA patients to consider whether or not to get surgery. Objective: To find out the relationship between AMH hormone and sperm retrieval rate of NOA patients undergoing surgical testicular sperm extraction. Method: PUBMED, EMBASE, CENTRAL, and Web of Science were utilized for overview knowledge. A host of studies were conducted to compare AMH biomarkers in NOA men undergoing the surgical testicular sperm extraction. Results: Serum AMH concentration is a potential biomarker to predict sperm retrieval rate for a subgroup of patients with idiopathic NOA or non-mosaic Klinefelter syndrome. However, The power of evidence is not strong enough due to small sample sizes and most studies being retrospective. In contrast, seminal AMH is not currently used as an effective biomarker predicting positive sperm retrieval rate. Conclusion: The available evidence is insufficient to help clinicians make adequate decisions support, and more prospective, large sample size, and multicenter trials are urgently needed.